(untitled) (Conferencea, 2024)
Protecting the rights and welfare of children is a cornerstone of any developed society. Across the globe, child protection systems aim to ensure the safety, well-being, and development of minors, particularly those in vulnerable circumstances. Guardianship and custodianship (trusteeship) institutions-commonly referred to as child welfare agencies-play a pivotal role in addressing the needs of minors, especially those subjected to neglect, abuse, or abandonment. The effective functioning of these institutions is not only a reflection of a country’s social priorities but also a legal obligation under international frameworks such as the United Nations Convention on the Rights of the Child (CRC). Article 3 of the CRC highlights that “in all actions concerning children... the best interests of the child shall be a primary consideration”. However, implementing these principles varies significantly across countries, shaped by cultural norms, legal systems, and resources.